2000
DOI: 10.2116/analsci.16.1247
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of NO2-Substituted Pyrenes by Liquid Chromatography-Atmospheric Pressure Chemical Ionization-Mass Spectrometry

Abstract: Polycyclic aromatic compounds (PACs) are widespread as environmental contaminants, and many of them have a high mutagenicity and carcinogenicity, suggesting that these compounds pose risks to human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Table 4 lists the nitro-PAH recovery rates of the overall analytical procedure (extraction, clean-up, and HPLC analysis) applied to spiked spark discharge soot samples (70-90% for the 12 measured compounds) and from standard diesel soot samples (80-90% for the four compounds listed in the original NIST Certificate of Analysis). The values are similar to those of the corresponding parent PAH investigated in this study (80-95%, [36]) and of nitro-PAH investigated in earlier studies (80-100%) using ultrasonic extraction [21] or different techniques like pressurized fluid extraction (PFE) and soxhlet extraction [29,47,48]. Due to the relatively high recovery rates and the lack of a suitable internal standard, no recovery correction was applied to the nitro-PAH measurement values reported below.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Table 4 lists the nitro-PAH recovery rates of the overall analytical procedure (extraction, clean-up, and HPLC analysis) applied to spiked spark discharge soot samples (70-90% for the 12 measured compounds) and from standard diesel soot samples (80-90% for the four compounds listed in the original NIST Certificate of Analysis). The values are similar to those of the corresponding parent PAH investigated in this study (80-95%, [36]) and of nitro-PAH investigated in earlier studies (80-100%) using ultrasonic extraction [21] or different techniques like pressurized fluid extraction (PFE) and soxhlet extraction [29,47,48]. Due to the relatively high recovery rates and the lack of a suitable internal standard, no recovery correction was applied to the nitro-PAH measurement values reported below.…”
Section: Resultssupporting
confidence: 85%
“…Analysis of nitrated polycyclic aromatic hydrocarbons by liquid chromatography with fluorescence and mass spectrometry detection: air particulate matter, soot, and reaction product studies nitrated pyrenes [29] and benzo[a]pyrenes [30] have been reported since then. Other mass spectrometric methods for the analysis of nitro-PAH include HPLC-MS with a particle beam interface (EI and CI) [31], HPLC-GC systems coupled to an atomic emission detector or an ion trap mass spectrometer [32,33], and UV laser desorption and ionization coupled to negative ion time-of-flight mass spectrometry (TOF-MS) [34].…”
Section: Christian Schauer · Reinhard Niessner · Ulrich Pöschlmentioning
confidence: 99%
“…The detection limit for 1-NP was 0.32 fmol/injection. This value is two orders of magnitude lower than the values obtained with recent HPLC methods with on-line reduction and fluorescence detection [21,22], the LC-atmospheric pressure chemical ionization (APCI)-MS method [23] and HPLC with electrochemical detection [24], and comparable…”
Section: Resultsmentioning
confidence: 62%
“…Nitrated PAHs can be detected more easily than PAHs by LC/MS, because the nitro group has a high polarity. Simultaneous determination of 1-nitropyrene, 1,3-, 1,6-and 1,8-dinitropyrene by LC/APCI/MS has been reported by Moriwaki et al (2000) [41]. In the report, the [M] -peaks of nitrated PAHs were observed by APCI in negative ion mode, and soil samples were determined to contain nitrated pyrene at the ng/g level by this method.…”
Section: Discussion 21 Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 98%